TECHNICAL EFFICIENCY OF WATERMELON FARMING IN BLAMBANGAN VILLAGE, MUNCAR SUB-DISTRICT, BANYUWANGI, EAST-JAVA, INDONESIA - Ade Yoga Pratama; Sujarwo Sujarwo (Agricultural Socio-Economics Journal, 2016)
Small-scale farmers in Blambangan Village, Banyuwangi, East Java, Indonesia take risk decision in growing watermelon. Assuming that farmers are rational, they will be able to overcome many obstacles regarding the risky watermelon farming. However, in term of efficiency farmers have vary among them and this is the interested topic to be observed more. In line with this thought, this study has several objectives: (1) to analyze the level of technical efficiency of the use of factors of production in farming watermelons in the research area, and (2) to analyze the ratio between actual input and optimum input that should be used in the research area. The method used is Data Envelopment Analysis (DEA) approach. The value of technical efficiency in this study is based on input-oriented and measurement of technical efficiency use DEA VRS (Variable Return to Scale). The results show that the average technical efficiency of respondent farmers are equal to 0.901. There are 11 respondents in state of Constant Return to Scale (CRS), 8 respondents in state of Increasing Return to Scale (IRS), and 2 respondents in state of Decreasing Return to Scale (DRS). There slack for all inputs used.